Boots and saddles : or, Life in Dakota with General Custer - Custer, Elizabeth Bacon, 1842-1933 (Digital Scanning, 1999)
"Boots and Saddles" is in reality a bright and sunny sketch of the life of Mrs. Custer's late husband, Gen. George A. Custer, who fell at the battle of the Little Big Horn. Readers will find a first-hand account of her frontier life as a wife of a cavalry officer on the plains